Developing 21st Century Competencies among Youth through an Online Learning Program: BE a Global Citizen - Macarena-Paz Celume; Haïfat Maoulida (Education Sciences, 2022)
Background: Within the current labor market, continuously changing and accelerating since the COVID-19 crisis (World Economic Forum, 2021), the educational system must offer a pedagogical alternative to face and anticipate these 21st century changes and demands (OECD, 2018). Based on the four-dimensional education framework, from the Center for Curriculum Redesign (CCR), the online learning literature, and students’ perspectives, the Beyond Education (BE) organization has proposed a series of interactive online pedagogical programs aiming to develop 21st-century competencies in school-age students. Methods: The aim of this paper is to propose both quantitative and qualitative data analyses of the first pilot program: “BE a Global Citizen” through a semi-experimental study, using a mixed-method approach, analyzing the pre- and post-tests results of 26 students aged 16 to 18 years old. Results: Analyses presented evidence of the program’s efficacy at developing 21st century competencies in students, particularly those competencies targeted by the program, which were significantly increased. Conclusions: Although these are promising results, a replicability study needs to be done on a larger sample in order to generalize the results.